Transnational Education in Chinese Secondary Education - Choon Boey Lim, Fion (International Higher Education, 2016)
This article discusses the development of transnational activities in the Chinese secondary school sector, particularly at the senior level. It describes how growth has outpaced quality control, and discusses the role that the China Centralised Government is likely to take in terms of future quality management.